Potensi Healing Hutan Kota Ranggawulung Kabupaten Subang - Geugeut Astika Cedec; Rachmad Hermawan; Siti Badriyah Rushayati (BIOEDUSAINS:Jurnal Pendidikan Biologi dan Sains, 2026)
This study aimed to identify biophysical potential and determine spots for developing healing activities in the Ranggawulung Urban Forest as an effort to utilize urban green spaces for the physical and mental health recovery of the community. This study used a field observation method by measuring biophysical parameters on two designated trails in the Ranggawulung Urban Forest, including air temperature and humidity, noise levels, wind speed, light intensity, slope inclination, canopy shade density, natural sounds, visual landscape beauty, and the presence of aromatic plants; data were analyzed descriptively and quantitatively, then synthesized to determine the most suitable time and spots for healing activities. The results showed that the most suitable time for healing activities is between 06:00 and 08:00 WIB, with the most suitable spots located in the middle and rear sections of both trails; the trails were arranged by connecting trail 1 and trail 2 to achieve a minimum trail length of 1 km, and the construction of a green belt in the front area of the urban forest along with the addition of dense-canopy trees are necessary to address noise problems and Temperature Humidity Index (THI) values that have not yet reached a comfortable category. This study concludes that Ranggawulung Urban Forest has adequate biophysical potential to be developed as a healing area, with a series of activities including walking through the forest, breathing fresh air, listening to nature sounds, hugging trees, sunbathing, inhaling the aroma of aromatic plants, emotional release, and meditation.  Keywords: Biophysics, Trail, Spot, Stress